Diabetes mellitus: new therapeutic approaches to treat an old disease - M.C. Sogayar (São Paulo State University (UNESP), 2005)
Diabetes mellitus is a widespread disease whose frequency increases constantly and is expected to reach alarming levels by the year 2025. Introduction of insulin therapy represented a major breakthrough; however, a very strict regimen is required to maintain blood glucose levels within the normal range and to prevent or postpone chronic complications associated with this disease. Frequent hyper- and hypoglycemia seriously affect the quality of life of these patients. Reversion of this situation can only be achieved through whole organ (pancreas) transplant or pancreatic islet transplant, the former being a high-risk surgical procedure, while the latter is a much simpler and may be accomplished in only 20-40 min. The advantages and perspectives of islet cell transplantation will be discussed, in the light of tissue engineering and gene therapy. Ongoing research carried out in our laboratory, aimed at developing clinical cell and molecular therapy protocols for diabetes will also be focused.